Women's Leadership in Education - Khasanah, Uswahtun; Istanto, Istanto (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This research aims to analyze women's leadership in Islamic education at Muhammadiyah Senior High School Special Program West City and its impact on the quality of education. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation. Data analysis was conducted through data reduction, presentation, and conclusion drawing. The research results show that the leadership strategies implemented positively impact student's academic achievements, as evidenced by the improvement in national exam results and the high acceptance rates of students in prestigious universities. In addition, teacher training programs and data-driven evaluation systems create a more innovative and inclusive learning environment. In conclusion, women's leadership in Islamic education cannot only overcome social and cultural challenges but also significantly contribute to improving academic quality and school governance